Construction and characterization of a camelized, human, VH-based peptide vaccine against CD20 antigen. (February 2013) - Liu, Jianbin; Tan, Yanguo; Zhang, Ranxing
Aim: The purpose of this study was to construct and characterize a camelized, human, heavy-chain variable (VH) fragment-based peptide vaccine against CD20 antigen.Materials & methods: Camelized, human VH with improved solubility and stability was used as a vaccine scaffold. A CD20 B-cell epitope was introduced into the complementarity determining region 3 of the engineered VH and a measles virus-derived T-helper epitope was grafted into the complementarity determining region 3. The chimeric VH fragment was synthesized in bacteria and purified for immunization of mice. The titers and antigen-binding specificity of the antibody elicited by the chimeric peptide vaccine were assessed in vitro .Results: Notably, the CD20 epitope within the chimeric VH peptide elicited high-titered anti-CD20 antibody. Besides binding to GST–CD20 fusion protein, the antibody was cross-reactive with the native CD20 antigen on Raji cells.Conclusion: In conclusion, the chimeric VH peptide vaccine consisting of the CD20 epitope can induce the production of the CD20-specific antibody, likely having potential implications in preventing CD20 overexpression cancers.